Sensitivity of the second seismic moments resolution to determine the fault parameters of moderate earthquakes - Cuius, Arianna; Meng, Haoran; Saraò, Angela; Costa, Giovanni (Frontiers in Earth Science, 2023)
Second-degree seismic moments provide a simple description of the spatiotemporal extent of the earthquake source. Finite source attributes such as rupture length, width, duration, velocity, and propagation direction can be estimated by computing second-degree seismic moments without the need for a predefined rupture model. This is achieved by analyzing the properties of apparent source time functions (ASTFs) obtained from seismic signals recorded at different stations after eliminating instrument responses and path effects. In this study, to define the limits of its application in the analysis of small earthquakes and to evaluate the sensitivity and reliability of the results to uncertainties due to observations and prior knowledge, we modeled a synthetic seismic source and examined how potential uncertainties in hypocentral depth, velocity model, focal mechanism, source duration, and number of recording stations can affect the inversion results. An accurate ASTF is essential to obtain robust results and our findings show that the mean values of the key source parameters, i.e., fracture size, source duration, and rupture velocity, are generally well reproduced in all sensitivity tests, with some exceptions, within the standard deviation. We also demonstrate that large uncertainties in the hypocentral depth and inaccurate velocity models introduce a significant bias, especially in rupture size and average centroid velocity, indicating the strong influence of ray path calculation in the inversion process. These resolution limits must therefore be taken into account when interpreting the results obtained with this technique.